Introduction: Continuing Legacies: Engaging Custodians in Heritage Conservation - Rahimah Abdul Aziz; Ong Puay Liu; Sarah Aziz; Sharina Abdul Halim (Kajian Malaysia, 2017)
This special issue of Kajian Malaysia on "Continuing Legacies: Engaging Custodians in Heritage Conservation" with focus in Malaysia is to draw attention to the multi-dimensional aspects of continuing legacies and the role of custodians that cross-cut various disciplines. The issue presents a collection of nine refereed research articles. They are written by a group of researchers from various disciplines and background of Faculties and Research Institutes at Universiti Kebangsaan Malaysia. Seven of the papers are written by the Governance and Education for Heritage Conservation Research Group members based on findings of their various research on the subject, while two papers are written by colleagues from other research groups but who are also focusing on heritage conservation. This is to emphasise that the success of heritage conservation requires multidisciplinary efforts and that heritage conservation should be a concern of all. It also underlines the fact that the success of any heritage conservation efforts depend on the combination of top-down, bottom-up grassroots approach.